Reactions Related to CAR-T Cell Therapy - Miao, Lele; Zhang, Zhengchao; Ren, Zhijian; Li, Yumin (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) T-cell therapy is a kind of tumor immunotherapy that has developed rapidly in recent years. It has achieved significant progress in hematological malignancies and has now begun to be used in the research and treatment of solid tumors. However, many adverse reactions often occur during the treatment, including cytokine release syndrome (CRS), CAR-T-cell-related encephalopathy syndrome (CRES), off-target effects, anaphylaxis, infections associated with CAR-T-cell infusion (CTI), tumor lysis syndrome (TLS), B-cell dysplasia, hemophagocytic lymphohistiocytosis (HLH)/macrophage activation syndrome (MAS) and coagulation disorders. Serious adverse reactions can even be life-threatening, so these adverse reactions need to be identified in time and treated effectively and correctly. This paper reviews some adverse reactions in the treatment process of CAR-T cells, their formation mechanisms, and coping strategies. It aims to provide some references for clinicians to better manage adverse reactions related to CAR-T cell therapy.